Response of vigna unguiculata.(L.) Walp. and amaranthus cruentus (L.) Thell to interference from acalypha segetalis mull arg. on marginal lands in southwestern Nigeria (2001)
The role of each weeds depends on weed type, density and duration of association with the crop as well as competitive ability of the crop. In open garden experiments, the phenology of Acalypha segetalis, a common weed of arable and ruderal habitats in south western Nigeria, and its influence on the growth and performance of Vigna unguiculata and Amaranthus cruentus, were investigated in 1999 and 2000. Acalypha segetalis was found to be slow growing in the first four weeks of its life cycle but developed rapidly and vigorously afterwords. It produced and shed seeds within 10 weeks of growth. Vigna unguiculata, which is highly susceptible to weed infestation in the first four weeks of growth, did not suffer significant growth and yield reductions from the association with j4 ca/yp/ia segetalis. However, Amaranthus cruentus, which has similar growth habits with the weed, suffered significant reductions in growth and yield. Amaranthus suffered up to 42% marketable yield loss when grown with Acalypha. The early slow growth of Acalypha determines its competitive potential in arable cropping systems. Crops that establish fast and with superior early growth ability may not suffer adverse competitive repression with the weed.